GROWTH AND RADIATION USE EFFICIENCY OF WHEAT AS AFFECTED BY DIFFERENT IRRIGATION LEVELS AND PHOSPHORUS APPLICATION METHODS - H. Ali; N. Tariq; S. Ahmad; M. Rasheed; T. H. Chattha; A. Hussain (Journal of Animal and Plant Sciences, 2012)
Effects of five irrigation treatments (I1 = control (no irrigation), I2 = two irrigations (crown root and booting stage), I3 =  three irrigations (crown root, booting and grain development), I4 = four irrigations (crown root, booting , anthesis and grain development), and I5 = five irrigations  (crown root, booting, earing, anthesis and grain development) and three phosphorus application methods (P1 = side dressing, 3 inches side the seed , P2 =  broadcasting at the time of seedbed preparation and P3 =  top dressing after first irrigation) on growth, light interception and light use efficiency of wheat were studied through field experiments conducted at experimental area of the Central Cotton Research Institute (CCRI), Multan, (30.12 oN, 71.28 oE, 123 m) during growing seasons of 2006-07 and 2007-08. Full irrigation treatments (I4 and I5) captured 510-488 MJ m-2 between 20 DAS and 120 DAS, by that time crop had achieved maximum biomass. In addition to light interception, treatments also affected radiation use efficiency (RUE). During both the seasons, highly significant linear relationship between cumulative intercepted photosynthetically active radiation (PAR) and biomass production was observed. Radiation use efficiency (RUE) of wheat ranged from 1.81-1.88 g MJ-1. Results revealed the highest grain yield (> 5 t ha-1) obtained from fully irrigated treatments (I4) while yield variations among irrigation levels were caused by affecting both the amount of intercepted PAR and RUE. Based on these results, application of four irrigations at crown root, booting, anthesis and grain development could be considered for improving RUE in spring wheat under a relatively hotter environment.
Keywords: Leaf area index; Pakistan; total dry matter accumulation; wheat.